A large scale hearing loss screen reveals an extensive unexplored genetic landscape for auditory dysfunction - Michael R. Bowl; Michelle M. Simon; Neil J. Ingham; Simon Greenaway; Luis Santos; Heather Cater; Sarah Taylor; Jeremy Mason; Natalja Kurbatova; Selina Pearson; Lynette R. Bower; Dave A. Clary; et al. (Nature Communications, 2017)
The full extent of the genetic basis for hearing impairment is unknown. Here, as part of the International Mouse Phenotyping Consortium, the authors perform a hearing loss screen in 3006 mouse knockout strains and identify 52 new candidate genes for genetic hearing loss.